Selective and efficient extraction of iron from water systems with a recyclable phytate-polyaniline hydrogel. (20th December 2022) - Tang, Chaoyun; Ramírez-Hernández, Maricely; Thomas, Belvin; Asefa, Tewodros
Abstract: Iron is an essential element for various physiological processes in our body. However consuming excess iron can affect our health. Thus, any excess iron that may be present in domestic water sources needs to be removed to make such water useable in the community. In this work, phytate-polyaniline hydrogel is synthesized with a simple method and then shown to selectively and efficiently adsorb and extract Fe ions (both in 2+ and 3+ forms) from aqueous solutions. The hydrogel can adsorb 99.94% of Fe from an aqueous solution containing 29.08 mg/L of Fe 3+ ions at pH = 7, and its maximum adsorption capacity for Fe is 0.841 mmol/g. Moreover, the hydrogel can do so even in the presence of many other common metal ions in water and in a wide pH range. In addition, the Fe adsorbed in the hydrogel can easily be removed via a simple procedure, and the hydrogel can be recycled and reused multiple times to remove Fe from aqueous solutions with nearly similar performances as the original material. Graphical abstract: Image 1 Highlights: A phytate-polyaniline hydrogel adsorbent is synthesized with a simple method. The hydrogel can efficiently adsorb and extract Fe ions from water systems. The hydrogel removes 99.9% of Fe from solutions in a wide pH range to treat water. The hydrogel adsorbs Fe ions in water more effectively than other common metal ions. The hydrogel can easily be recycled and reused multiple times to extract iron ions.